Vacancy durations: A model for employer's search - Andrea Weber (Institute for Advanced Studies (IHS), 1997)
This paper investigates a Dutch data set on vacancy durations and numbers of applicants to inquire employer's search strategies. A non-sequential search process assumes that most vacancies are filled from a pool of applicants, which is formed shortly after the posting of the vacancy. The time spent on recruiting applicants and the duration of the selection process are estimated with a proportional hazard model, via the arrival - and attrition rates of applicants.
Keywords: C2; C5; J6; 330; vacancy durations; numbers of applicants; attrition; Offene Stellen; Personalbeschaffung; Theorie; Niederlande